2017
DOI: 10.1093/nar/gkx101
|View full text |Cite
|
Sign up to set email alerts
|

Rad6–Bre1-mediated H2B ubiquitination regulates telomere replication by promoting telomere-end resection

Abstract: Rad6 and Bre1, ubiquitin-conjugating E2 and E3 enzymes respectively, are responsible for histone H2B lysine 123 mono-ubiquitination (H2Bub1) in Saccharomyces cerevisiae. Previous studies have shown that Rad6 and Bre1 regulate telomere length and recombination. However, the underlying molecular mechanism remains largely unknown. Here we report that H2BK123 mutation results in telomere shortening, while inactivation of Ubp8 and/or Ubp10, deubiquitinases of H2Bub1, leads to telomere lengthening in Rad6–Bre1-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 71 publications
2
21
0
Order By: Relevance
“…3c (see lanes 8, 9 and 10), telomeres were also slightly longer compared to the wild-type for all DUBm mutant. This is consistent with a recent study demonstrating that inactivation of both Ubp8 and Ubp10 promotes telomere elongation (Wu et al 2017b). Since the phenotype of elongated telomeres are shared by all DUBm, our results suggest that Ubp8 activity takes place in the context of the DUBm as a complete module, by playing a relevant role in telomere homeostasis in yeast.…”
Section: Additional Factors In Trex-2 and Saga Affect Telomere Lengthsupporting
confidence: 94%
See 1 more Smart Citation
“…3c (see lanes 8, 9 and 10), telomeres were also slightly longer compared to the wild-type for all DUBm mutant. This is consistent with a recent study demonstrating that inactivation of both Ubp8 and Ubp10 promotes telomere elongation (Wu et al 2017b). Since the phenotype of elongated telomeres are shared by all DUBm, our results suggest that Ubp8 activity takes place in the context of the DUBm as a complete module, by playing a relevant role in telomere homeostasis in yeast.…”
Section: Additional Factors In Trex-2 and Saga Affect Telomere Lengthsupporting
confidence: 94%
“…However, a precise correlation between telomere length and global H2B monoubiquitination levels is unknown. The data presented in this study, together with recent work in humans and yeast (Armour et al 2013;Atanassov et al 2016;Wu et al 2017b) suggested that a normal cycle of ubiquitination and deubiquitination of H2BK123, as has been found for other proteins (Chu et al 2016;Jiang 2016;Nostramo and Herman 2016), influences telomere length. Thus, we decided to investigate whether mutants with short telomeres, such as rsc2Δ, resulted in a depletion of H2BK123ub 1 .…”
Section: Short Telomere Mutants Rsc2δ and Est1δ Show Low Levels Of H2supporting
confidence: 77%
“…Also, telomere elongation may depend on X-ray repair cross-complementing protein 3 (XRCC3) and NBS1 in stem cells (169). The MRX complex may also assist Rad6 and Bre1 ubiquitin-conjugating enzymes in successful telomere replication (170). …”
Section: Mrn and Dysfunctional Telomeresmentioning
confidence: 99%
“…One copy of RIF1 was deleted in BY4743 by a pRS306-rif1Δ cassette as descried previously (Liu et al, 2016;Wu et al, 2017). Rif1-5UTR-F & T7 and Rif1-orf-F& Rif1-orf-R were used to confirm RIF1 deletion.…”
Section: Yeast Strains Plasmids and Primersmentioning
confidence: 99%